Development of different drug delivery systems for skin regeneration - Morgado, Patrícia Isabel da Cruz (2013)
The human body has different fluids that are hostile environments for biologically active molecules. To overcome this arbitrary, several drug delivery systems have been developed. These systems not only protect all unstable biological active compounds from enzymatic degradation in the human body but also allow a sustained and targeted release of drugs. They contribute for decreasing drug dose required to achieve the desired therapeutic effect. Hydrogels, with their important characteristics, have been widely used in the development of these systems however, the quantity of drug loaded into them may be limited and the high water content of these polymeric matrices often results in relatively rapid drug release profiles. Nevertheless, due to their good physical and biological properties, hydrogels have been extensively used in the treatment of skin injuries. In order to take advantage of hydrogels for drug delivery and wound healing, different systems (nano and micrometric) have been developed and incorporated into hydrogels matrices. Nano and micro systems exhibit high encapsulation efficiencies of drugs and allow its release for a long period of time. Thus, the main goals of this master thesis work plan were to develop micrometric systems based on chitosan, alginate and a dextran hydrogel, and characterize their applicability in the treatment of skin injuries. Initially, the carriers were characterized according to their size, geometry, swelling behavior and biocompatibility. In vitro release studies allow us to analyze the release profile of a model protein (bovine serum albumin) when encapsulated into the microparticles. The same studies were done for microparticles loaded into a dextran hydrogel. Co-relating the swelling studies with the in vitro protein release studies a mathematical model based on the theory of hindered transport of large solutes in hydrogels was developed for theoretically describing the process of protein release. All the experimental results were interpreted with the aid of the developed model. Moreover it can contribute to decrease the number of experimental studies, reducing costs and saving time for the carrier development. After that, growth factors (vascular endothelial growth factor and endothelial growth factor) were encapsulated into chitosan microparticles that were then loaded into the dextran hydrogel. Subsequently in vivo studies were performed to characterize the applicability of the dextran hydrogel loaded with chitosan microparticles containing growth factors in wound healing. The in vitro and in vivo studies demonstrated that the developed carriers are biocompatible, accelerate the wound healing process and can be used to deliver other bioactive agents.